PENGARUH EKSPOR, IMPOR DAN INVESTASI SYARIAH TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA PERIODE 2011-2018 - Andi Triyawan; Mutmainnah Mutmainnah (ANALISIS, 2021)
Economic growth is driven by exports, imports, and syariah investment. Research aims to determine the effect of export, import, and syariah investment to Indonesia’s economic growth period 2011-2018. Indonesia economic growth always change. This study use quantitative method. The data used is time series subject during of 2011-2018 from Central Bureau of Statistics. Analysis of the subject in this study using multiple linear regression analysis. Simultaneous test results show that exports, imports, and syariah investment has not a significant influence on economic growth of Indonesia. For partial test, exports are negative and significant, imports are negative but not significant, and syariah investment are negative and significant to economic growth of Indonesia period 2011-2018.